2002
DOI: 10.1271/bbb.66.1256
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of Fructosyl-amino Acid Oxidase Gene fromCorynebacteriumsp. 2-4-1 inEscherichia coli

Abstract: The gene encoding the fructosyl-amino acid oxidase (fructosyl-alpha-L-amino acid: oxygen oxidoreductase (defructosylating); EC 1.5.3) of Corynebacterium sp. 2-4-1 was cloned and expressed in Escherichia coli. The gene consists of 1,116 nucleotides and encodes a protein of 372 amino acids with a predicted molecular mass of 39,042. The open reading frame was confirmed as the gene of the fructosyl-amino acid oxidase by comparison with the N-terminal amino acid sequence of the purified fructosyl-amino acid oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…The activity for Fru-Gly was not high compared with that of FAOX-C (5.4 unit W mg). 15) We found that the AgaE-like protein acted on Fru-Val and Fru-Gly, but the main substrate for this protein in Agrobacterium cells is unclear. Genetic studies suggested that an Agrobacterium sp.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The activity for Fru-Gly was not high compared with that of FAOX-C (5.4 unit W mg). 15) We found that the AgaE-like protein acted on Fru-Val and Fru-Gly, but the main substrate for this protein in Agrobacterium cells is unclear. Genetic studies suggested that an Agrobacterium sp.…”
Section: Discussionmentioning
confidence: 84%
“…This enzyme was 54z identical in sequence to that of FAOX-C, which we characterized previously. 15) Table 3 summarizes the properties of AgaE-like protein (this study), FAOX-C, 13) and fungal FAOX-A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17][18] It has also been reported [19][20][21] that a fructosyl-peptide oxidase (FPO) is active for the oxidative deglycation of fructosyl amino acids and fructosyl peptides.…”
mentioning
confidence: 99%